A mastofauna do estado do Rio de Janeiro, com especial referência à ordem Polyprotodontia (Marsupiais) - Tribe, Christopher James (1987)
The aim of this dissertation, part of a wider study to determine the mammals of Rio de Janeiro state, Brazil, is to lay the foundations for future taxonomic work. The density-independent factors that might affect species' presence are reviewed, as is the history of mammal collecting and studies since the 16th century. A provisional species list for the state is also given. To exemplify the treatment to be given to the rest of the mammal fauna, the thirteen local species of Polyprotodontia are examined and described, with the aid of multivariate discriminant methods based on measurements of the marsupial skulls in the Museu Nacional collection, Rio de Janeiro. These analyses provide important results for the study of within-species variation and the formation of biogeographical hypotheses.